Corn Processing with Design of Flaters Machinery and Diversification of Corn Processing with Andaliman Flavor (Zanthoxylum Acanthopodium) in Parsaoran Village, Sibisa, Toba Samosir Regency - Purba, Sukarman; Rahmi, Ana; Harahap, Khairunnisa (Talenta Publisher, 2022)
The objectives to be achieved in PKM activities; developing corn farmers' businesses in Parsaoran Sibisa Village to become economically independent businesses through processing andaliman flavored corn chips, designing and building corn flattening machines, training on corn chips production, business management training and packaging. The specific target to be achieved through a corn flattening machine is to increase the effectiveness of the abundant corn production into andaliman corn chips, savory, sweet, spicy, able to manage business and packaging. The approach method used is the method of education, production training, business management training, design and assistance. The results of this service activity by providing knowledge, technology and business management, corn farmers are expected to be able to take advantage of their agricultural products which are processed into high-value corn chips products. Corn chips are a food diversification product that can support the development of rural agro-industry and increase the income value of corn farmers whose raw materials are easily available in Parsaoran Sibisa Village, Toba Samosir Regency.